2017
DOI: 10.33736/ijbs.534.2016
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Financial Constraints in Family Controlled Firms: Evidence From Malaysia

Abstract: The hypothesis of financial constraints suggests that firms will be denied profitable investment dueto inaccessible to external capital markets as debt and equity financing are no longer perfectsubstitutions after firms utilize internal capital. In view of reduced investments during globalfinancial crisis in 2008-2009, the study investigates 157 firms, whether they face the issues offinancial constraints in Malaysia. In general, non-family firms rely heavily on the external debtmarket while family controlled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…Observation showed that non-family firms rely heavily on debt, in contrast with family-controlled firms which are mobilizing internal funds and reduce dependency on debt. This confirms that pecking-order constraints exist in family firms (Chu, Lai, & Song, 2016) . On the other hand, observations showed that asymmetric information has a significant impact on firms' short-term and total capital structure (Newman, Gunessee, & Hilton, 2012).…”
Section: Literature Reviewsupporting
confidence: 77%
“…Observation showed that non-family firms rely heavily on debt, in contrast with family-controlled firms which are mobilizing internal funds and reduce dependency on debt. This confirms that pecking-order constraints exist in family firms (Chu, Lai, & Song, 2016) . On the other hand, observations showed that asymmetric information has a significant impact on firms' short-term and total capital structure (Newman, Gunessee, & Hilton, 2012).…”
Section: Literature Reviewsupporting
confidence: 77%
“…They also discover that during financial crises, investment in non-family owned firms and return on investment are higher in non-family controlled firms. The same is also reported by Chu et al (2016), who studied Malaysian family-controlled firms during the global financial period of 2007-08. After using regression analysis, it was discovered that family firms are more financially constrained than non-family-controlled firms due to low investment efficiency in family-controlled firms.…”
Section: Literature Review and Hypothesis Development 21 Ownership St...supporting
confidence: 75%
“…Hanazaki and Liu (2007) and Lins et al (2013) conclude that financial constraints are more severe in family-owned firms as large shareholders are more inclined to look upon their interests at the cost of minority shareholders. The same is also endorsed by Chu et al (2016), who studied Malaysian family-controlled firms and suggested a positive impact on financial constraints. Further, ownership concentration is positively associated with financial constraints as in those firms; there is a high level of information asymmetry and less governance disclosure; which in turn increases the level of financial constraints (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations